Nutritious dishes from the garden - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Improving nutrition through home gardening. A training package for preparing field workers in Africa FAO, 2001. 282 pp. ISBN 9251043884 US$ 22 Euro 24.55